-3=x+x+1+x+2

Simple and best practice solution for -3=x+x+1+x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=x+x+1+x+2 equation:



-3=x+x+1+x+2
We move all terms to the left:
-3-(x+x+1+x+2)=0
We add all the numbers together, and all the variables
-(3x+3)-3=0
We get rid of parentheses
-3x-3-3=0
We add all the numbers together, and all the variables
-3x-6=0
We move all terms containing x to the left, all other terms to the right
-3x=6
x=6/-3
x=-2

See similar equations:

| 3|2x+1|=12 | | -2x+4=4x-1 | | 45(p^2-1)=56 | | -(1-3p)=-(1+6p) | | 1/3+k=7/3 | | 3y2+6y–6=0 | | -8x-x+5=-6x+5=3 | | 3x³+21x+30=0 | | 0=|x-1|-2 | | -12-3s=7s+18 | | 2a-14=3(a+1)+18a+3 | | 3/2y=36 | | X+15x=21500 | | -8-5(6n+11)=3(-n+6) | | 0.25q+0.10(2q+6)=10.95 | | 7/5p=-12/9 | | 4-3(2a+3)+5a=-a-5 | | 9-4k=15-k | | -5x=(5/3) | | 8x+20=4(x+12) | | 14x/(x+3)=7 | | 4y-36=12-× | | 1=1/3(18x+3) | | 6x2+5x-4=0 | | -6v-12(v-9)=12(6v-6) | | X^2(x-7)+18(x-7)=0 | | 5z+1=99 | | -17x-20=-13×+120 | | -4(x+1)-12=10+16 | | 2p-3+p-4+1=p | | -2(4a-8)=0 | | 2p-3+p-4=p |

Equations solver categories